Barter in Transition Economies: Competing Explanations Confront Ukrainian Data - Dalia Marin; Daniel Kaufmann; Bogdan Gorochowskij (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2000)
In this paper we survey the common explanations of barter in transition economies and expose them to detailed survey data on 165 barter deals in Ukraine in 1997. The evidence does not support the notion that soft budget constraints, lack of restructuring, or that the virtual economy are the driving forces behind barter. Further, tax avoidance is only weakly associated with the incidence of barter in Ukraine. We then explore an alternative explanation of barter as a mechanism to address transitional challenges where capital markets and economic institutions are poorly developed. First, barter helps to maintain production by creating a deal-specific collateral which softens the liquidity squeeze in the economy when credit enforcement is prohibitively costly. Second, barter helps to maintain production by preventing firms to be exploited by their input suppliers when suppliers' bargaining position is very strong due to high costs of switching suppliers. Thus, in the absence of trust and functioning capital markets barter is a self-enforcing response to imperfect input and financial markets in the former Soviet Union. The paper concludes by discussing potential long-term costs of barter arrangements, and by suggesting particular pitfalls of expansionary monetary policy in barter economies such as Ukraine and Russia.
urn:nbn:de:bvb:19-epub-63-5
Keywords: 330; barter; transition economies; tax avoidance